The role of stock prices and market efficiency in predicting future profitability on the Tehran Stock Exchange - Yasin Fattahi; Mohammad Rahimpour (New Applied Studies in Management, Economics & Accounting)
This study investigates the role of stock price and market efficiency in forecasting future profitability. In pursuit of this objective, the study undertook a comprehensive analysis of data derived from a robust statistical sample of 152 firms, encompassing a total of 1,520 firm-year observations. The data collection period for this research spans nine years, from 2013 to 2022; however, owing to the reliance on data from the subsequent three years for the measurement of the dependent variable, the analytical scope is refined to encompass the years 2013 through 2018. The statistical population comprises all firms listed on the Tehran Stock Exchange (TSE), from which the research sample was meticulously selected utilizing a systematic screening method. To effectively address the research objectives, advanced analytical techniques, including multiple regression analysis and panel data methods, were employed. The findings suggest that market efficiency positively moderates the relationship between return on assets and future profitability. However, the results show that the interaction between market efficiency and firm market value, as measured by the logarithm of Tobin's Q ratio, does not significantly affect future profitability. Based on these findings, it can be concluded that market efficiency has no significant impact on the ability of stock prices to predict firms' future profitability.